Effect of gender on training-induced vascular remodeling in SHR - Amaral, Sandra Lia do [UNESP]; Michelini, L. C. (Associação Brasileira de Divulgação Científica (ABRADIC), 2011)
There is accumulating evidence that physical inactivity, associated with the modern sedentary lifestyle, is a major determinant of hypertension. It represents the most important modifiable risk factor for cardiovascular diseases, which are the leading cause of morbidity and mortality for both men and women. In addition to involving sympathetic overactivity that alters hemodynamic parameters, hypertension is accompanied by several abnormalities in the skeletal muscle circulation including vessel rarefaction and increased arteriole wall-to-lumen ratio, which contribute to increased total peripheral resistance. Low-intensity aerobic training is a promising tool for the prevention, treatment and control of high blood pressure, but its efficacy may differ between men and women and between male and female animals. This review focuses on peripheral training-induced adaptations that contribute to a blood pressure-lowering effect, with special attention to differential responses in male and female spontaneously hypertensive rats (SHR). Heart, diaphragm and skeletal muscle arterioles (but not kidney arterioles) undergo eutrophic outward remodeling in trained male SHR, which contributed to a reduction of peripheral resistance and to a pressure fall. In contrast, trained female SHR showed no change in arteriole wall-to-lumen ratio and no pressure fall. on the other hand, training-induced adaptive changes in capillaries and venules (increased density) were similar in male and female SHR, supporting a similar hyperemic response to exercise.
Keywords: Exercise training; Hypertension; Microcirculation; Arterioles; Capillaries; Venules